Pelaksanaan Pendidikan Kesehatan Kader Dan Keluarga Dalam Upaya Mengoptimalkan Tugas Keluarga Untuk Pencegahan Komplikasi Hipertensi Di RW 2 Kelurahan Bangsal Kediri - Srinalesti Mahanani; Erlin Kurnia (Pelita Medika, 2021)
Background : The one part of controlling hypertension is improving the quality of human resources, especially in case management and program management. Health education is an effort to achieve this. One of the health education that can be given is health education for health workers and non-health workers in controlling hypertension sufferers. Efforts to train non-health workers, in this case are cadres. Method : The approach method used is lecture and discussion methods and monitoring is carried out every month. Results : From the data obtained from 30 elderly, 67% or 20 elderly have a good level of knowledge. It can be seen that the elderly are more aware of their hypertension condition and the family patiently escorts the elderly to do check-ups at the posyandu for the elderly. After being given health education on efforts to optimize family duties in providing care for the elderly with hypertension to prevent complications in RW 2, Ward Ward, Kediri City when helping cadres and family members in increasing knowledge of the elderly, so that the family understands how to care for the elderly with hypertension and the elderly also understand how to treat the elderly with hypertension. Conclusion : It is hoped that the cadres will be more active in providing information to the elderly about the importance of posyandu activities and health checks, and cadres can provide health education to the elderly about health.